Indian Food Information Input to International Food Information Service: An Information Analysis Case Study - Ranganath, K. A.; Seetharam, Geetha; Sangameswaran, S. V.; Narahari Rao, B. S. (Journal of Information and Knowledge, 1981)
Information published in the area of Food Science and Technology from India has been analysed. The experience gained in sending the Indian input to International Food Information Service has also been analysed and the usefulness of such a collaboration has been delineated. This analysis has brought out the change in the concept of food technology between the international abstracting service and the national service. This analysis also pointed out the areas of most active research in food field based on the information available in published articles.